2001
DOI: 10.1111/j.1749-6632.2001.tb05646.x
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Learning and Memory in Rats Caused by Oxidative Stress and Aging, and Changes in Antioxidative Defense Systems

Abstract: To elucidate the influence of oxidative stress on the brain functions during aging, the cognitive performance ability of rats was assessed by using the water-maze test as an oxidative stress before and after hyperoxia. Young rats showed significantly greater learning ability than both old rats and vitamin-E-deficient rats. Although the memory functions of all rats were impaired after oxidative stress, the memory retention of young rats was greater than those of other groups. After the stress, none of the rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
110
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 246 publications
(121 citation statements)
references
References 8 publications
9
110
0
1
Order By: Relevance
“…Furthermore, deficiency of vitamin E accelerates oxidative damage in the brain. Vitamin E-deficient rats have lower activity of antioxidant enzymes and increased lipid peroxidation in the brain (10,11). It is possible that enhancement of oxidative damage of vitamin E-deficient models affects autophagy.…”
Section: Increased Expression Of Map-lc3 In the Cerebral Cortex And Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, deficiency of vitamin E accelerates oxidative damage in the brain. Vitamin E-deficient rats have lower activity of antioxidant enzymes and increased lipid peroxidation in the brain (10,11). It is possible that enhancement of oxidative damage of vitamin E-deficient models affects autophagy.…”
Section: Increased Expression Of Map-lc3 In the Cerebral Cortex And Hmentioning
confidence: 99%
“…In a previous study, we demonstrated that vitamin E-deficient rats exhibited cognitive dysfunction in several maze tasks (10,11). We have been studying the mechanisms of cognitive dysfunction in this animal model, and have found evidence of apoptosis and b-amyloid-like proteins in the hipocampal CA1 region (12), indicating that cognitive dysfunction in vitamin E-deficient animals may be connected with injury to hippocampal neurons.…”
mentioning
confidence: 99%
“…In another study, it was shown that free O 2 radicals increased in diabetic rat brains, and these increased O 2 -free radicals were decreased using an ET-1 antagonist [57]. Long-term oxidative damage leads to morphological damage and memory disorders in many parts of the brain [58,59], and one previous study showed that diabetes-induced hippocampal neuron damage was prevented by antioxidant therapy [60]. As an indicator of lipid peroxidation and oxidative stress, MDA levels were found to be quite high in the diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that young rats subjected to hyperoxia as oxidative stress reveal marked deficits in learning and memory functions, and that the delayed-type apoptosis of pyramidal cells is induced after oxidative stress [8]. These abnormalities are also observed in both old rats and vitamin E-deficient young rats not subjected to oxidative stress [9].…”
Section: Introductionmentioning
confidence: 90%